Dental pulp stem cells promote regeneration of damaged neuron cells on the cellular model of Alzheimer's disease. (11th April 2017) - Wang, Feixiang; Jia, Yali; Liu, Jiajing; Zhai, Jinglei; Cao, Ning; Yue, Wen; He, Huixia; Pei, Xuetao
Abstract: Alzheimer's disease (AD) is an incurable neurodegenerative disease and many types of stem cells have been used in AD therapy with some favorable effects. In this study, we investigated the potential therapeutical effects of human dental pulp stem cells (hDPSCs) on AD cellular model which established by okadaic acid (OA)‐induced damage to human neuroblastoma cell line, SH‐SY5Y, in vitro for 24 h. After confirmed the AD cellular model, the cells were co‐culture with hDPSCs by transwell co‐culture system till 24 h for treatment. Then the cytomorphology of the hDPSCs‐treated cells were found to restore gradually with re‐elongation of retracted dendrites. Meanwhile, Cell Counting Kit‐8 assay and Hoechst 33258 staining showed that hDPSCs caused significant increase in the viability and decrease in apoptosis of the model cells, respectively. Observation of DiI labeling also exhibited the prolongation dendrites in hDPSCs‐treated cells which were obviously different from the retraction dendrites in AD model cells. Furthermore, specific staining of α‐tubulin and F‐actin demonstrated that the hDPSCs‐treated cells had the morphology of restored neurons, with elongated dendrites, densely arranged microfilaments, and thickened microtubular fibrils. In addition, results from western blotting revealed that phosphorylation at Ser 396 of Tau protein was significantly suppressed by adding of hDPSCs. These results indicate that hDPSCs may promote regeneration of damaged neuron cells in vitro model of AD and may serve as a useful cell source for treatment of AD.